2021
DOI: 10.3389/fmicb.2021.710526
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of the Gradient Diffusion Strip Method and Disk Diffusion Method for Ceftazidime–Avibactam Against Enterobacterales and Pseudomonas aeruginosa: A Dual-Center Study

Abstract: Objectives: Ceftazidime–avibactam is a novel synthetic beta-lactam + beta-lactamase inhibitor combination. We evaluated the performance of the gradient diffusion strip method and the disk diffusion method for the determination of ceftazidime–avibactam against Enterobacterales and Pseudomonas aeruginosa.Methods: Antimicrobial susceptibility testing of 302 clinical Enterobacterales and Pseudomonas aeruginosa isolates from two centers were conducted by broth microdilution (BMD), gradient diffusion strip method, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
2
5
1
Order By: Relevance
“…According to our findings, the CZA Etest for Enterobacterales isolates yielded a CA, EA, ME and VME of 100%, 97%, 0% and 0%, respectively, which is in agreement with those previously reported when using the EUCAST breakpoint (CA, EA, ME and VME of 100%, 100%, 0% and 0%, respectively) [24]. Earlier observations have also supported the appropriate performance of the Etest for CZA AST against Enterobacterales following the CLSI criteria [25][26][27].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…According to our findings, the CZA Etest for Enterobacterales isolates yielded a CA, EA, ME and VME of 100%, 97%, 0% and 0%, respectively, which is in agreement with those previously reported when using the EUCAST breakpoint (CA, EA, ME and VME of 100%, 100%, 0% and 0%, respectively) [24]. Earlier observations have also supported the appropriate performance of the Etest for CZA AST against Enterobacterales following the CLSI criteria [25][26][27].…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, applying the EUCAST breakpoints, previous studies have reported VME rates of 4.5–7.2%, corroborating our results [ 24 , 28 ]. Of note, no VMEs were noted with the CLSI breakpoints [ 25 , 26 ], highlighting the impact of the criteria applied for AST interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Concerningly, the ceftazidime-avibactam automated susceptibility system is not widely applied in China, and the reference broth microdilution (BMD) method is difficult for routine microbiology laboratories to perform. Although Etest has demonstrated exemplary performance for ceftazidime-avibactam susceptibility testing with Enterobacterales and P. aeruginosa isolates ( 11 13 ), it is costly. To sum up, the disk diffusion test is the optimal option in most laboratories, because it is convenient, economical, and practical; however, there are some drawbacks to the disk diffusion test, such as different specifications and manufacturers, subjective measurements, and inoculum effects.…”
Section: Introductionmentioning
confidence: 99%
“…Results from antimicrobial susceptibility testing (AST) and resistant bacteria identification (ID) are regarded as the definitive data in diagnosis of the infectious diseases. Disk diffusion [5], gradient diffusion [6], antibiotic strips [7], broth microdilution [8], and so on are considered current golden standard methods that are accurate and sensitive. However, these approaches rely on complicated and redundant pre‐analytical processing of the samples [9].…”
Section: Introductionmentioning
confidence: 99%